Faktor – Faktor Yang Mempengaruhi Kecemasan Keluarga Pasien Pada Saat Dilakukan Triage Di IGD RSUD Dr. Haryoto Lumajang - Zainal Abidin; Widya Addiarto; Yeni Andriani; Mariani (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
The large number of patient visits to the emergency room requires a triage system to sort out patients who are prioritized to get service first to anticipate patient overcrowding and avoid patients who are not helped or die due to not getting fast help. The distribution of triage is one of the common causes for families to feel anxious. Moreover, if the family does not understand the triage system used, they will feel ignored and afraid if their family members do not get health services immediately. This study aims to determine the anxiety of the patient's family when triage is carried out in the emergency room. This study used an observational design with a cross-sectional approach, a sample of 95 people. Data collection used a questionnaire. Bivariate analysis used the Chi Square test. Multivariate analysis used the Logistic Regression Test. The statistical test results obtained a p value = 0.05, namely there is a response time relationship. nurses with patient family anxiety during triage in the ER, there is a relationship between nurse therapeutic communication and patient family anxiety during triage in the ER, there is a relationship between patient knowledge/information and patient family anxiety during triage in the ER, there are factors that have the most influence to the level of anxiety. There is a relationship between nurse response time, there is a relationship with nurse therapeutic communication, there is a relationship with patient knowledge/information and the factors that most influence the anxiety level of the patient's family when triage is carried out in the emergency room of RSUD dr. Haryoto Lumajang is a nurse therapeutic communication factor. Keywords: Anxiety of the patient's family, Triage, Emergency Department